Designação e dessignificação: a filiação de sentidos na fraseologia contemporânea - Vargas, Rejane Maria Arce (2011)
In this study, which belongs to the scope of French Discourse Analysis developed in Brazil from the works of Orlandi, we aim to discuss the issue of sense filiation. So we took as a sample the current discursivization of the nomination community/shantytown, conceived as a mistaken pair by the assumption of a tacit replaceability of shantytown by community, reinforced by its wide circulation and social coverage. These two words, textualized in a discursive reference sequence, are the point from where we organized a discursive assembly, constituted by distinct discursive registers, collected from digital media between the years 2009 and 2010, which were selected due to the serial circulation of the names community and shantytown and also to the relationship with discursive reference sequence. Thus, it forms a representative net of the current ways of circulation in which discourses are under the impact of the new ITs, which bring as a balance a metallic memory that contributes for the flattening of discursive memory. The way we organized the corpus in its dynamic dimension allows us to postulate a conception of contemporary phraseology marked by designification, marked by the deletion of political sense, what happens through metallic agencies of the social memory and of a cynical idea of social peace and consensus, which becomes effective, for example, by the process of designation.